0968 Sleep Architecture and Breathing Disturbances in Comorbid Anxiety and Depression. (27th April 2018) - BuJáki, B; Ray, L; Saad, M; Lee, E; Douglass, A; DeKoninck, J; Robillard, R
Abstract: Introduction: Comorbidity rates between anxiety disorders and depression are high. In case-control studies, atypical sleep features have been attributed to anxiety disorders or depression, but little is known about the diagnostic specificity of these features and the sleep signature of anxious-depressive comorbidity. Depression and anxiety have several common sleep abnormalities, such as increased REM sleep and decreased NREM3 sleep. This study aimed to compare the sleep profile of anxiety and depression when occurring independently or in conjunction in a population with sleep complaints. Methods: A retrospective polysomnography database of individuals referred to a sleep clinic was used to identify individuals: (1) without diagnosed mental disorders and asymptomatic on the Beck Depression Inventory-II (BDI<14; Control), with a history of (2) anxiety disorder, (3) unipolar depressive syndrome and BDI≥14, and (4) both anxiety disorder and unipolar depressive syndrome and BDI≥14 (Comorbid). Each group contained 95 individuals matched for age and sex (58% females, mean±SD: 44 ± 13 years old). Sleep architecture and respiratory disturbance indexes (RDIs) were compared across groups. Results: There was a significant increase in sleep onset latency across groups (Control < Anxiety< Depression < Comorbid). The Anxiety and Depression groups had similarly longer REM latencies than the Control group, and this was further lengthened in the Comorbid group. The Comorbid group showed significantly lower %REM than all other groups, but there was no significant %REM difference between the Control, Anxiety, and Depression groups. No significant difference in RDIs was seen between the Control, Anxiety and Depression groups, but the Comorbid group showed significantly higher RDIs than both the Control and Anxiety groups. Conclusion: These results contrast with previous findings for REM and NREM3. Few differences were observed between people with anxiety and those with depression, but those with anxious-depressive comorbidity were found to have more severe sleep alterations, including worse sleep-related breathing disturbances. While this should be confirmed by longitudinal studies, anxiety disorders may complicate the manifestation of sleep disturbances linked to depression, and vice-versa. Future studies should decipher the contribution of psychoactive medication on these interactions. Support (If Any): N/A.